DEVELOPMENT AND EVALUATION OF MICROSPONGE GEL OF AN ANTIFUNGAL DRUG - S., GUNASHEELA; CHANDRAKALA, V.; SRINIVASAN, S. (International Journal of Current Pharmaceutical Research, 2023)
Objective: The objective of the present study was to compare the release effect of Luliconazole from different polymeric (Hydrophilic and Hydrophobic) microsponges prepared using varying concentrations. The best microsponge was selected and incorporated into different gel (Natural and synthetic) and drug release is determined and compared with marketed formulation. Methods: Polymers such as EC, HPMC, Eudragit RSPO and PVA as emulsifier, and solvent DCM is used as solvent. Microsponge were prepared by using the quasi emulsion solvent diffusion technique. FTIR was studied to estimate the incompatibility. Microsponges were evaluated for SEM, particle size, drug content, and In vitro diffusion studies. Optimized microsponge incorporated gel was prepared by using different gel (flax seed gel and Aerosil gel) were evaluated for pH, spreadability, extrudability, drug content and in vitro diffusion studies. Results: Theresults obtainedshowed no physical-chemical incompatibility between the drug and the polymers. EC, HPMC and EC combination was found to be a suitable polymer compared to Eudragit RSPO and other combination in preparation of microsponge. From the evaluation of microsponge, the optimized F1 formulations was incorporated into different gel (flax seeds, aerosil) and compared with marketed formulation in which MG-I (flax seed gel) was considered as good topical anti-fungal microsponge gel based on there physical parameters and drug release kinetics. Conclusion: Microsponge and microsponge gel were successfully prepared for Luliconazole and their evaluation studies of each dosage form revealed that topically applied microsponge gel possess immense potential to control the release rate of medicament to improve the bioavailability as well as patient compliance.